Simple Damage Potential of Earthquake with Low Frequency Content Based on Global Reinforced Concrete (RC) Inelastic Response. (2017) - Pawirodikromo, Widodo
Abstract: A numerical investigation was conducted on the damage potential of 25-low frequency content ground motions (earthquake) normalized to be the maximum of 0.30 g. The damage potential is measured based on several parameters started from the simplest parameter (Level-1) to the complex parameter (Level-5). The global inelastic response of 10-story RC structure subjected to the corresponding ground motions, i.e the base shear, roof horizontal displacement, hysteretic energy and element damage index, have been used as damage indicators. Then, the ground motion parameters were correlated with the damage indicators. Results of the investigation showed that among the damage indicators are well correlated. The A/V ratio is relatively simple parameter (Level-2) and possesses relatively consistent and high correlation coefficient R with the damage indicators. Accordingly, A/V ratio can be stated as simple damage potential to cause severity of the structure under earthquake excitation.